On the impact of the operational and technical characteristics of the LaRa experiment on the determination of Mars' nutation. (January 2020) - Le Maistre, S.; Péters, M.-J.; Marty, J.-C.; Dehant, V.
Abstract: LaRa is a radio-science payload of the ExoMars 2020 mission. The LaRa instrument consists of an X-band transponder accompanied by a set of three antennas and three RF cables, all mounted on the stationary ExoMars surface platform. This instrument is designed to measure with a couple of mHz of accuracy the Doppler shift induced by the variations in Mars rotation and orientation on a direct-to-Earth round-trip radio link. The main scientific objective of the LaRa experiment is to constrain the interior structure of Mars by precisely measuring the nutations of the planet's spin axis. LaRa's measurements will also be used to refine the rotation model of Mars and infer constraints on the dynamic of its atmosphere. This paper aims at characterising the impact of different parameters, related to the design of the LaRa instrument itself and to its operations, on the determination of the rotation and orientation parameters of Mars, and especially on the nutation parameters. Among other quantities, we analyze the effects of the measurements noise, the tracking pass length and occurrence, the mission duration, the radio signal elevation and azimuth in the lander sky, the blackout periods, and the onboard power availability. The work is a comparative study, where we examine different scenarios/cases with respect to a nominal one. From this study, general conclusions can be drawn on the nutation determination from direct-to-Earth Doppler data provided by a landed mission (like InSight). This study provides quantitative inputs that can be used for the programmatic and operation strategy of a radio-science experiment from a lander. In particular, we show that regular tracking from both East and West sides of the lander (i.e. at Earth-rises and Earth-sets) is mandatory to best fit the rotation parameters. Since power issues are frequent on solar-powered landers, we might have to wait for the spacecraft batteries to recharge before operating LaRa. This study shows that turning on LaRa up to one hour after sunrise (i.e. ≤ 15 ∘ of Sun elevation) is acceptable, while requiring higher elevation of the Sun to operate LaRa would significantly reduce its science return. One can finally mention that blackout periods of any kind would compromise the scientific achievement of the LaRa experiment if last too long (hundreds of days). Highlights: LaRa (Lander Radio-science) is a scientific payload of the ExoMars 2020 mission. Sensitivity analysis of the LaRa experiment to Mars' nutation parameters. Impact of different parameters related to LaRa design and operations. Inputs for programmatic and operation strategy of lander radio-science experiments.